If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = 10x + 6 Reorder the terms: 7 + 5x = 10x + 6 Reorder the terms: 7 + 5x = 6 + 10x Solving 7 + 5x = 6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 7 + 5x + -10x = 6 + 10x + -10x Combine like terms: 5x + -10x = -5x 7 + -5x = 6 + 10x + -10x Combine like terms: 10x + -10x = 0 7 + -5x = 6 + 0 7 + -5x = 6 Add '-7' to each side of the equation. 7 + -7 + -5x = 6 + -7 Combine like terms: 7 + -7 = 0 0 + -5x = 6 + -7 -5x = 6 + -7 Combine like terms: 6 + -7 = -1 -5x = -1 Divide each side by '-5'. x = 0.2 Simplifying x = 0.2
| 4(x+7)+9=64 | | 50-25X=0 | | 4x+7+9=64 | | 8n+9=n | | 3u-u=12 | | V=y/u | | Uy=-10 | | 10(4x)=640 | | -3u=z | | P(x)=-2/3x^2 | | U/z=y | | -3x-3x+8=-22 | | 2y=4(-3)+14 | | -3(-x-4)=-36 | | 2 = s3– 2 | | 23-2X=15 | | p=2g | | X+8X+28=1 | | 75x+25x=22x | | 10x-7x=24 | | Y/u=a | | 24-2X=22 | | 9=x+x+7 | | 6k-2s=4s-12 | | 2ac-5b= | | (7x+4)=(10x-28) | | -1/6*(-9/7) | | 4y^2=5v+6 | | 15x-20=x+10 | | X+2(4x+14)=1 | | 3b^2=2b+5 | | 18x^3-12x^2/6x^2 |